Burnout dimension profiles among healthcare workers in Indonesia. Issue 3 (March 2023) - Lamuri, Aly; Shatri, Hamzah; Umar, Jahja; Sudaryo, Mondastri K.; Malik, Khamelia; Sitepu, Monika S.; Saraswati,; Muzellina, Virly N.; Nursyirwan, Saskia A.; Idrus, Muhammad F.; Renaldi, Kaka; Abdullah, Murdani
Abstract: Background: Besides biological impact, COVID-19 also poses a threat to psychological wellbeing and the quality of life. Healthcare workers, especially those assuming a front-line post, are at a higher risk of being affected, both physically and psychologically. This study aims to analyse variables potentially associated with burnout and psychological distress among healthcare workers with various health center stratifications, where we commenced a nationwide survey to establish the baseline data. Method: An analytic observational study with a cross-sectional design was conducted on the 11th – September 18, 2020. Participants were enrolled from healthcare institutions represented by epicenter of the COVID-19 pandemic in Indonesia, which were Java, Sumatra, Bali, and were asked questionnaires, including the Depression, Anxiety and Stress Scale 21 (DASS-21), Maslach Burnout Inventory (MBI), Somatic Symptom Scale 8 (SSS-8), also Well-Being Index (WBI). A linear mixed effect model was used to analyse how three dimensions of burnout vary across occupations. Results: A total of 3629 healthcare workers were analysed in this study. Burnout syndrome was found in 37.5% of healthcare workers. The prevalence of burnout among medical personnel, nurses, and midwives was 44.6%, 33.5%, and 36.2%, respectively. The prevalence of burnout in healthcare workers was most common in Java (38.4%) and healthcare workers who work in the hospital (28.6%). Based on the burnout dimensions, 48.2% of healthcare workers experienced moderate to high emotional exhaustion, 51.8% moderate to high depersonalization, and 96.9% high personal accomplishment. The R 2 values was 0.33, 0.28, 0.27 for emotional exhaustion, depersonalization and personal accomplishment model. Calculated power of the emotional exhaustion and depersonalization model was 100% for both midwife and nurse variable. Meanwhile, the power of the personal accomplishment model was 100% for midwife and 94.7% for nurse variable. Conclusion: The extent of the three burnout dimensions is pervasive in all occupational levels and the place of work (hospital/community health center).